Evaluating Airline Performance through Financial Ratios and the Balanced Scorecard: A Comparative Study of Singapore Airlines and Garuda Indonesia - La Himmah il Princess Choris (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
The post-pandemic recovery of the airline industry requires performance evaluation that captures not only financial outcomes but also strategic resilience, customer trust, operational efficiency, and organizational capability. This study aims to compare the performance of Singapore Airlines and Garuda Indonesia during 2019–2023 using an integrated financial ratio and Balanced Scorecard approach. The study applies a quantitative-descriptive comparative design based on secondary data from the annual reports of both airlines. Financial performance is assessed through profitability indicators, including return on assets, return on equity, net profit margin, and operating profit margin, while the Balanced Scorecard evaluates four perspectives: financial, customer, internal business process, and learning and growth. The results show that both airlines experienced severe disruption during 2020–2021, followed by recovery in 2022–2023. Singapore Airlines demonstrated a more stable and consistent recovery across all performance dimensions, supported by stronger profitability, service reputation, operational discipline, and workforce productivity. Garuda Indonesia also showed significant improvement, particularly in revenue and operating profit, but its recovery followed a deeper decline and appeared more dependent on restructuring, external intervention, and short-term efficiency measures. These findings indicate that airline recovery cannot be adequately explained by financial ratios alone. A multidimensional framework is needed to distinguish temporary financial rebound from sustainable strategic resilience. This study contributes to airline performance measurement literature by offering an integrated model for assessing post-crisis recovery and provides practical insights for airline managers, regulators, and investors seeking sustainable aviation strategies.